A Community-Engaged Approach to Reducing Barriers to Breast and Cervical Cancer Screening: The Use of Mapping Tools - Sally Moyce; Danika Comey; David Claudio; Maria Velazquez; Genesis Chavez Reyes; Elizabeth Aghbashian (Journal of Participatory Research Methods)
Visual tools such as diagrams and mapping are effective research methods that help engage the community in the process and encourage active participation in generating potential solutions to a complex health problem. In participatory research, these methods help bridge potential communication gaps between community partners and academics. We present the steps we undertook to evaluate barriers to completing recommended breast and cervical cancer screenings. We engaged a community advisory board (CAB) of women who had been enrolled in the National Breast and Cervical Cancer Early Detection Program to investigate barriers to receiving recommended screenings and to brainstorm potential solutions to address the barriers. We describe the tools we used in the process: fishbone diagrams, mind mapping, and concept mapping. We were able to identify and categorize potential solutions to increase screening rates under four themes: 1) communication; 2) scheduling; 3) transportation; and 4) providers. Real-time updates and feedback loops facilitated by these tools create a continuous dialogue between researchers and community partners, which strengthens the relationship between academic and community collaborators and ensures that the research remains responsive to the evolving dynamics of the community.